The THE EFFECT OF MOTIVATION AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE IN PT. LBUM - Simajuntak, Sufriadi; Tobing, Suzanna Josephine (Universitas Kristen Indonesia, 2017)
Human resources ( resources ) is one of the very important in organization, anything shape and its aims, the organization built upon the range of vision for the benefit of man and in the performance of its mission managed and administered by humans.For that developed and human resources should be noted that the quality of human resources it can be improved, that resulted in an increase in the company ( organization ) where human resources are located.Discusses performance employees to remain with the factors that can influences the performance someone like motivation and how strong organization inside a culture of these organisations. As for the purpose of this study is to find relationship with employee performance motivation , cultural relations organization and employee performance , motivation and cultural the organization of employee performance in PT .Sumatra Berlian Utama Motor. This research is deskriptif-korelasional with a population of about 100 and samples from 50 employees and data diananlisis using analysis rank spearman and the correlation between. This research result indicates that ( 1 ) there is a significant relation of the incentives with with employee performance pt .The main diamond motor .This is shown by analysis rank spearman obtained correlation value of 0,289 with the significant ( sig .( 2-tailed ) ) 0,41 & it; standard significant 0,05 .( 2 ) there is a significant relation exists between cultures organization with with the performance of employees of pt .The main diamond motor .This is shown by analysis rank spearman obtained correlation value of 0,356 with the significant ( sig .( 2-tailed ) ) 0,11 & it; standard significant 0,05. Based on the research done , we can conclude that motivation and cultural company organization weak and need to be increased .Superior and employees to motivate organization that cultural stay awake and performance will increase .While in the performance has run well and should be maintained. Keywords: motivation and cultural on performance employees